"Bilingual Always": A Study of Second Language Writing's Influence on Writing Studies in the Canadian Association for the Study of Discourse and Writing/l’AssociationCanadienne de Rédactologie - Wright-Taylor, Christin (Discourse and Writing/Rédactologie, 2023)
Paul Kei Matsuda (2013) argues that due to a disciplinary division between applied linguistics and composition, modern iterations of language-based theories in composition lack accountability from knowledgeable peers. This article applies Matsuda's critique of U.S. Composition to a Canadian context. By conducting archival research on one of Canada's only two writing studies organizations, Canadian Association for the Study of Discourse and Writing / l’Association Canadienne de Rédactologie (CASDW-ACR), this project seeks to discover if the same disciplinary divide has existed between writing studies and L2 writing. The findings show that, unlike U.S. Composition, writing studies in Canada has long been open to and relied on L2 writing to establish itself as a discipline in Canadian higher education. The opportunities afforded by this historic partnership between writing studies and L2 writing should be intentionally built on in Canadian writing curriculum as internationalization introduces new translingual, visa students to the Canadian writing classroom.